Inventarisasi Jamur Tingkat Tinggi (Basidiomycetes) di Gunung Singgalang Sumatera Barat - Indra Anggriawan; - Periadnadi; - Nurmiati (Universitas Andalas, 2014)
The macrofungi of Basidiomycetes was collected in Singgalang mountain and then identified in Microbiology Laboratory, Department of Biology, Faculty of Sciences, Andalas University. The aim of this study was to identify the macrofungi from Basidiomycetes. This study used direct survey method to collect macrofungi from the field. This study identified 22 genera which belong to 10 family and 6 orders. Most of the fungi were belong to subclass of Hymenomycetidae.Keywords: basidiomycetes, inventories, macrofungi.